علماء المغرب الإسلامي ودورهم في بلاد السودان الغربي 05-10 هـ/ 11-16 م - سالمي، زينب Salmi, Zainab (جامعة طاهري محمد بشار - مخبر الدراسات الصحراوية, 2012)
Business relationship between Islamic Maghreb and Western Sudan had a big role in strengthening the cultural and scientific links. This was clear in several Maghreb ins’ trips to this country as tradesmen, scholars and religious men to spread Islam in a new land to be a victory for Muslims. As a matter of the fact, Arab-Islamic civilisation had been prospered in Western Sudan and there were universities and academies in Timbuktu, Gao, as big as the scientific centers in Islamic Maghreb in: Fez, Zaytuna, Telemcen...
لقد كانت للعلاقات التجارية بين بلاد المغرب الإسلامي وبلاد السودان الغربي دور كبير في توثيق الصلات الثقافية والعلمية وتجلى ذلك في الرحلات التي قام بها العديد من المغاربة إلى هذه البلاد كتجار وعلماء وفقهاء لنشر الدين الاسلامي وفتح بلاد جديدة لتكون نصرا للمسلمين وبالفعل ازدهرت الحضارة العربية الاسلامية في بلاد السودان الغربي وأصبحت لها جامعات ومعاهد تضاهي المراكز العلمية في بلاد المغرب الاسلامي مثل فاس، تلمسان، الزيتونة.. وأهم مراكزها تمبكتو غاو..
Keywords: بلاد السودان الغربي -- المغرب الإسلامي -- الدعوة الإسلامية -- الطرق الصوفية -- الزوايا